Intensity adaptive optics - Zhao, Z; Ma, Y; Song, Z; Antonello, J; Cui, J; Chen, B; Wang, J; Sun, B; He, H; Luo, L; Fells, JAJ; Elston, SJ; et al. (Springer Nature, 2025)
Adaptive optics (AO) is a powerful tool employed across various research fields, from aerospace to microscopy. Traditionally, AO has focused on correcting optical phase aberrations, with recent advances extending to polarisation compensation. However, intensity errors are also prevalent in optical systems, yet effective correction methods are still in their infancy. Here, we introduce a novel AO approach, termed intensity adaptive optics (I-AO), which employs a dual-feedback loop mechanism to first address non-uniform intensity distribution and subsequently compensate for energy loss at the pupil plane. We demonstrate that I-AO can operate in both sensor-based and sensorlessformats and validate itsfeasibility by quantitatively analysing the focus quality of an aberrated system. This technique expands the AO toolkit, paving the way for next-generation AO technology.